Ultrathin CuF2‐Rich Solid‐Electrolyte Interphase Induced by Cation‐Tailored Double Electrical Layer toward Durable Sodium Storage. (24th January 2023) - Song, Keming; Wang, Xiang; Xie, Zhengkun; Zhao, Zhiwei; Fang, Zhe; Zhang, Zhengfeng; Luo, Jun; Yan, Pengfei; Peng, Zhangquan; Chen, Weihua
Abstract: Solid‐electrolyte interphase (SEI) seriously affects battery's cycling life, especially for high‐capacity anode due to excessive electrolyte decomposition from particle fracture. Herein, we report an ultrathin SEI (3–4 nm) induced by Cu + ‐tailored double electrical layer (EDL) to suppress electrolyte consumption and enhance cycling stability of CuS anode in sodium‐ion batteries. Unique EDL with SO3 CF3 ‐Cu complex absorbing on CuS in NaSO3 CF3 /diglyme electrolyte is demonstrated by in situ surface‐enhanced Raman, Cyro‐ TEM and theoretical calculation, in which SO3 CF3 ‐Cu could be reduced to CuF2 ‐rich SEI. Dispersed CuF2 and F‐containing compound can provide good interfacial contact for formation of ultrathin and stable SEI film to minimize electrolyte consumption and reduce activation energy of Na + transport. As a result, the modified CuS delivers high capacity of 402.8 mAh g −1 after 7000 cycles without capacity decay. The insights of SEI construction pave a way for high‐stability electrode. Abstract : An ultrathin and CuF2 ‐rich solid‐electrolyte interphase is formed on CuS anode via Cu cation‐tailored double electrical layer in NaSO3 CF3 /diglyme electrolyte, which ensures high ion‐conductivity and greatly suppresses the electrolyte continuous decomposition. The modified CuS enables high reversible capacity and ultralong cycling life for sodium‐ion batteries.